Process innovation in partnering: A framework for aligning organizational cultures in the Malaysian construction industry - Abdul Nifa, Faizatul Akmar; Ahmed, Vian (2014)
Partnering has been formally introduced in the Malaysian construction industry since the year 2009 as a measure to cure the industry's many diseases.Although the Public Private Partnership Unit (3PU) and the Construction Industry Development Board (CIDB) Malaysia has proposed their own models for partnering, these models do not address the need for similarity in organizational cultures among partnering organizations to ensure partnering success as suggested by several studies. In response to this challenge, and consistent with the requirements of the construction industry to perform better in terms of innovation and productivity, this paper aims to propose a framework for enabling the partnering process which meets the needs of different organizational culture within the Malaysian construction industry.The framework is based on the findings from a recent postgraduate study on the engagement of Malaysian construction firms in partnering practices. The findings concluded that although the government has made the effort in introducing partnering, the industry has not fully embraced this method due to dissimilarities in organizational culture among firms involved and several partnering enablers are yet to be present in the industry.